1998
DOI: 10.1063/1.122338
|View full text |Cite
|
Sign up to set email alerts
|

Atomic transport across the interfaces during the formation of ultrathin silicon oxide/nitride/oxide films

Abstract: The redistribution of O and N during the final, thermal oxidation in dry O2 step in the formation of ultrathin silicon oxide/nitride/oxide dielectric films (ONO) was investigated using isotopic tracing and depth profiling with nanometer resolution. The results show that the final oxidation step induces atomic transport of O and N species in the system, such that the formed ONO structures are not stacked layer structures, but rather a silicon oxynitride ultrathin film, having moderate concentrations of N in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…In a previous work 19 we addressed the usefulness of isotopic substitution and depth profiling with nanometric resolution in the investigation of the atomic transport across the interfaces during the formation steps of ultrathin ONO structures. Those results already sug- Isotopic tracing was used to determine the distribution of O and N after the final fabrication step of ultrathin silicon oxide/nitride/ oxide (ONO) films, revealing how the processing parameters affect the characteristics of the resulting structure.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous work 19 we addressed the usefulness of isotopic substitution and depth profiling with nanometric resolution in the investigation of the atomic transport across the interfaces during the formation steps of ultrathin ONO structures. Those results already sug- Isotopic tracing was used to determine the distribution of O and N after the final fabrication step of ultrathin silicon oxide/nitride/ oxide (ONO) films, revealing how the processing parameters affect the characteristics of the resulting structure.…”
mentioning
confidence: 99%
“…In a previous work 19 we addressed the usefulness of isotopic substitution and depth profiling with nanometric resolution in the investigation of the atomic transport across the interfaces during the formation steps of ultrathin ONO structures. Those results already sug-S0013-4651(99)02-035-2 CCC: $7.00 © The Electrochemical Society, Inc.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works 13,14 have reported N and O mobility during thermal oxynitridation in NO of thermally grown SiO 2 films on Si. They showed that during the NO process, besides incorporation of N near the SiO 2 / Si interface, there is also atomic exchange between oxygen from the gas phase ͑NO͒ and oxygen from the SiO 2 film.…”
mentioning
confidence: 99%